Instructional design research trends towards digital transformation of education systems in ASEAN - Jajang Kusnendar; Deni Darmawan; R. Rusman (Inovasi Kurikulum, 2024)
The curriculum implementation in ASEAN countries is interesting to examine, especially in order to achieve the direction of the digital transformation roadmap of the education system. Research on instructional design can be used as one of the parameters to understand how the general description of implementation achieves curriculum goals. This study aims to examine instructional design research in ASEAN countries during the period 2018-2024 on the implementation of the national curriculum towards the digital transformation of the education system through (1) investigating the general description of instructional design research, (2) examining research characteristics from aspects of research objectives, (3) explaining the implications of findings both theoretically and practically. The documentation study was conducted through bibliometric analysis of articles with keywords against article titles containing the phrase "instructional design" in ASEAN countries from the Scopus database, which produced as many as 37 selected articles during the 2018-2024 period. The results show that the general description and direction of instructional design research objectives in ASEAN countries have been presented comprehensively. Besides that, the theoretical and practical implications of instructional design research on the road map for digital transformation of education systems in ASEAN have been considered. AbstrakImplementasi kurikulum di negara ASEAN menarik diteliti khususnya dalam upaya mencapai arah peta jalan transformasi digital sistem pendidikan. Riset tentang instructional design bisa dijadikan salah satu parameter untuk memahami bagaimana gambaran umum implementasi untuk mencapai tujuan kurikulum. Penelitian ini bertujuan untuk mengkaji riset instructional design di negara ASEAN selama periode 2018-2024 pada implementasi kurikulum nasional dalam menuju transformasi digital sistem pendidikan, melalui: (1) investigasi gambaran umum penelitian instructional design, (2) mengkaji karakteristik penelitian dari aspek tujuan penelitian, (3) menjelaskan implikasi temuan baik secara teoritis maupun praktis. Studi dokumentasi dilakukan melalui analisis bibliometrik terhadap artikel dengan kata kunci terhadap judul artikel yang mengandung frasa “instructional design” di negara ASEAN, dari database scopus yang menghasilkan sebanyak 37 artikel terpilih selama periode tahun 2018-2024. Hasil menunjukan bahwa gambaran umum dan arah tujuan penelitian instructional design di negara ASEAN telah tersaji secara komprehensif, selain itu implikasi teoritis dan praktis dari riset instructional design terhadap peta jalan transformasi digital sistem pendidikan di ASEAN sudah dianggap sejalan.Kata Kunci: bibliometrik; desain pembelajaran; kurikulum; pendidikan; transformasi digital